Sirtuin 1 in Chronic Kidney Disease and Therapeutic Potential of Targeting Sirtuin 1 - Yan, Jiayi; Wang, Jue; He, John Cijiang; Zhong, Yifei (Frontiers in Endocrinology, 2022)
The incidence and prevalence of chronic kidney disease (CKD) continue to increase worldwide remaining as a major public health burden. CKD eventually progresses to end-stage kidney failure and patients with CKD have high morbidity and mortality. Sirtuin 1 (SIRT1), a NAD+-dependent deacetylases, has significant renal protective effects through its regulation of fibrosis, apoptosis, and senescence, oxidative stress, inflammation and aging process. The renal protective effects of Sirt1 have been described in many kidney diseases such as diabetic kidney disease and HIV-related kidney disease. SIRT1 also has protective effects against vascular calcification and therefore could be developed as a therapy for both CKD and CKD complications. In this narrative review, we will give an overview of the recent progress on the role of SIRT1 and its downstream pathways in CKD. We will also discuss potential therapeutic approach by activating SIRT1-related pathway in patients with CKD. The purpose is to hope to provide some insights on the future direction of the research in the field of SIRT1 for CKD.